Creatinina sérica como factor pronóstico de complicaciones maternas en pacientes con preeclampsia - Tasso Tapia, Renzo Antonio (2017)
Demostrate if serum creatinine is used to predict maternal complications in patients with preeclampsia. MATERIAL AND METHOD: Was conduced an analitic, diagnostic test, observational, retrospective, investigation. The study population was conformed for 222 pregnant women hospitalized in the obstetrics service at “Hospital Belén de Trujillo” in the period January 2014 - December 2014 according to established inclusion and exclusion criteries. The population constituted the sample. With serum creatinine data is constructed a ROC curve, a cut-off point for serum creatinine was determined, the area under the curve was calculated and diagnostic values such as sensitivity, specificity, positive predictive value and negative predictive value were determined. RESULTS: The cut-off point determined by the ROC analysis was 0.795 mg/dl. The area under the ROC curve was 0.855 with a 95% CI 0.802-0.899. The sensitivity was 79.37% with a 95% CI 68.58-90.15 and the specificity was 78.62% with a 95% CI 71.93-85.30. CONCLUSION: Serum creatinine is a test with a good ability to discriminate patients with preeclampsia who will develop complications of which they do not, with an area under the curve of 0.855